Pleistocene population expansions of shade-tolerant trees indicate fragmentation of the African rainforest during the Ice Ages. Issue 1866 (1st November 2017) - Piñeiro, Rosalía; Dauby, Gilles; Kaymak, Esra; Hardy, Olivier J.
Abstract : The fossil record in tropical Africa suggests that dry conditions during the Ice Ages caused expansion of savannahs and contraction of the rainforest. Forest refugia have been proposed to be located in areas of Central Africa that currently harbour high rates of endemic species. However, to what extent the forest was fragmented remains unknown. Nuclear microsatellites and plastid sequences of 732 trees of two species occurring in the same habitat—mature lowland evergreen rainforests—but with remarkably different dispersal capacities—animal versus gravity—were analysed. Geographical information system tools revealed intraspecific lineages partially congruent across the two species, suggesting common past barriers to gene flow in Central Africa. According to approximate Bayesian computation, the intraspecific genetic clusters diverged during the Pleistocene (less than 2 Ma), so that intraspecific differentiation is the appropriate scale to test the aridification effect of the Ice Ages on tree populations. Demographic tests revealed clear genetic signals of population expansion in both taxa, possibly following bottleneck events after forest fragmentation, with stronger evidence of expansion after the Penultimate rather than after the Last Glacial Maximum. The differential dispersal capacity may have modulated the particular response of each species to climate change, as revealed by the stronger evidence of expansion found in the animal-dispersed species than in the gravity-dispersed one.